Faktor Penyebab Kejenuhan Belajar Siswa SMP Kelas VIII Pada Pembelajaran Bahasa Indonesia - Trisnawati Trisnawati; Diena San Fauziya (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This research aims to determine the factors that cause learning boredom in class VIII middle school students in Indonesian language subjects and the efforts that teachers must make to overcome student learning boredom. The method used in this research is descriptive qualitative. Data collected through observation and interviews. The research techniques used are data reduction, data presentation and drawing conclusions. The results of research on the factors that cause student learning boredom are the method of delivering material that is too monotonous, Indonesian language subjects that are less popular, tight class hours and heavy learning evaluations. Meanwhile, efforts that must be made by teachers are using varied learning methods, doing ice breaking, approach to students, a fun learning atmosphere, and occasionally learning outside the classroom.